Comparison of hematologic data in world elite junior speed skaters and in non-athletic juniors - Mayr, A.; Kuipers, H.; Falk, M.; Santer, P.; Wierer, B. (International Journal of Sports Medicine, 2006)
During the world junior speed skating championship 2002 all athletes (60 males, 56 females) were subjected to hematologic blood testing one day before the competition as requested by International Skating Union - ISU. This study aimed to obtain hematological reference values for junior athletes, whilst the influence of endurance training on hematologic variables of young athletes was studied. Hematologic results of athletes were compared to results of non-athletes matched by age and gender (14 males, 17 females). The blood analysis was done on an ADVIA 120. To compare measurement of ferritin, erythropoietin, and soluble transferrin receptor in serum as well as in EDTA-plasma, serum and EDTA-blood was obtained from the control group. In hemoglobin and hematocrit we found no significant difference between the two groups, whereas the number of erythrocytes was lower in athletes. The mean corpuscular volume was higher in athletes, whilst the corpuscular hemoglobin content was only marginally higher in athletes than in non-athletes. Consequently corpuscular hemoglobin concentration mean was lower in athletes than in non-athletes. There was no difference of erythropoietin and soluble transferrin receptor, whilst in ferritin we found a difference between the groups. Endurance training does not change the values of hemoglobin and hematocrit. Increased mean corpuscular volume and decreased corpuscular hemoglobin concentration mean could be a result of changed properties of red blood cell-membrane caused by acidosis and higher osmolality during the training. In junior athletes we did not find an iron overload as described in some adult athletes.